The Boy(s) Who Cried Wolf: Re-Visioning Textual Re-Presentations of Boys and Literacy - Baskwill, Jane; Church, Susan; Swain, Margaret (Atlantis, 2009)
This paper presents a narrative analysis of some current educational textual representations, including provincial documents, publisher materials, and stories from the field, that demonstrate concern for boys has become a master myth that idealizes and reinforces neo-conservative notions of masculinity. This gender binary is not helpful for boys nor girls and we offer some alternative considerations.